Uncommon Bilateral Absence of Long Heads of the Biceps Tendons in Twin Sisters: A Report of 2 Cases. Issue 3 (July 2021) - Kwapisz, Adam; Xu, Mark; Koenig, James; MacDonald, Peter; McRae, Sheila; Marsh, Jonathan
Abstract : We present 2 cases, 45-year-old identical twin sisters, with bilateral congenital absence of the long head of the biceps tendon (LHBT); 1 twin was symptomatic, while the other was not. Variations of the intra-articular portion of this tendon are widely reported, but there are few reports of cases with absent LHBT. These cases may be of particular interest to radiologists and surgeons because they demonstrate that absent biceps when congenital in nature may not always coincide with symptoms.